Intergeneration cooperation in Kyrgyzstan: Babushka Adoption project - Zhanybekova, Malika (Magyar Gerontológia, 2024)
Kyrgyzstan is a country in Central Asia with a population of 6.5 million. Projections suggest that by 2030, the proportion of Kyrgyz citizens aged 65 and over will be near 7%. According to United Nations criteria a population is classified “ageing”, when individuals aged 65 and over comprise more than 7% of the total population.